The Effect of Services Deductibility on VAT Compliance - Boryana Madzharova; Thiess Buettner; Orlando Zaddach (ZBW - Leibniz-Informationszentrum Wirtschaft, 2019)
This paper provides an empirical analysis of the effectiveness of tax subsidies implemented by the German government as a measure to combat evasion of taxes on services purchased by private households. Based on a theoretical analysis of the choice between formal and informal provision of services, we provide a difference-in-difference analysis which contrasts the VAT performance of firms in industries, whose services have become deductible from the income tax, with the VAT performance of other firms. We use the German VAT taxpayer panel and employ different identification strategies. A first set of results focuses on the construction sector and exploits the fact that only purchases of firms that specialize in specific services are subsidized. A second strategy focuses on the VAT performance of industries that are particularly prone to evasion. Our results point at significant effects of the tax deduction. In particular, we find some evidence that taxable sales relative to input VAT increase. This indicates that the increase in sales is not simply a demand effect from subsidized services. Rather, firms seem to respond at the formal-informal margin and a larger fraction of sales is carried out formally and taxed.
Keywords: H26; H24; 330; Tax compliance; VAT; Tax deductibility; Shadow economy; Informal sector